Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21009/jmt.4.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Penentuan Derajat Optimum Interpolasi pada Metode Lagrange dan Metode Newton Gregory dalam Mengestimasi Kasus Pasien Sembuh dari Covid-19 di Indonesia

Abstract: Estimation is one method for approximation. The estimation method is the polynomial interpolation. Once of polynomial interpolation are Lagrange method and Newton Gregory method. In several references, the degrees of interpolation which is used on the Lagrange method or Newton Gregory method depends on the numbers of data. This paper was created to knowing the optimum degrees to interpolate 61 numbers of data. In this paper, points are determined to interpolate so that formed intervals of equal length. As for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…From Table 3, it can also be concluded that the 2 nd order polynomial interpolation method is the most effective to use in forecasting gold prices because the smallest MAE, RMSE, and MAPE values are 6.895, 4.562, and 0.434% respectively. The results of this study are in line with the research of (Lamabelawa, 2019;Muhammad Julian et al, 2022). This suggests that a polynomial of 2 nd order has been able to model and forecast gold price fluctuations well.…”
Section: Conclusion and Suggestionsupporting
confidence: 88%
See 1 more Smart Citation
“…From Table 3, it can also be concluded that the 2 nd order polynomial interpolation method is the most effective to use in forecasting gold prices because the smallest MAE, RMSE, and MAPE values are 6.895, 4.562, and 0.434% respectively. The results of this study are in line with the research of (Lamabelawa, 2019;Muhammad Julian et al, 2022). This suggests that a polynomial of 2 nd order has been able to model and forecast gold price fluctuations well.…”
Section: Conclusion and Suggestionsupporting
confidence: 88%
“…MAE, RMSE, and MAPE are measures of forecasting error used to measure how far the forecasting results are from the actual value. The smaller the MAE, RMSE, and MAPE values, the more accurate the polynomial interpolation forecasting model used (Lamabelawa, 2019;Muhammad Julian et al, 2022). The following are the formulas given for MAE, RMSE, and MAPE:…”
Section: Evaluating the Accuracy Of The Polynomial Interpolation Modelmentioning
confidence: 99%
“…Jika Polinomial Newton menggunakan data yang berjarak sama maka Polinomial Newton Gregory Maju dapat ditulis sebagai Persamaan (3) berikut (Pratiwi, et. al., 2017;Julian, et. al., 2022, Balqis, et.…”
Section: Polinomial Newton Gregory Majuunclassified
“…Penurunan rumus Interpolasi Polinomial Newton Gregory Mundur sama dengan penurunan rumus Interpolasi Polinomial Newton Gregory Maju, dengan demikian diperoleh persamaan Interpolasi Polinomial Newton Gregory Mundur sebagai berikut Julian, et. al., 2022):…”
Section: Polinomial Newton Gregory Mundurunclassified
“…Kebisingan dalam jangka waktu yang lama bisa menyebabkan beberapa gangguan kesehatan (Siswati, 2017) [3]. Penilitian ini dilakukan dengan tujuan untuk mengetahui volume kendaraan pada ruas Jalan Raya Pantura pada ruas Kecamatan Pucuk -Kecamatan Sukodadi tahun 2023, mengetahui besar tingkat kebisingan yang ditimbulkan pada Jalan Raya Pantura pada ruas Kecamatan Pucuk -Kecamatan Sukodadi pada tahun 2023, mengetahui korelasi antara volume kendaraan dengan tingkat kebisingan [5] pada Jalan Raya Pantura pada ruas Kecamatan Pucuk -Kecamatan Sukodadi pada tahun 2023, dan memetakan volume kendaraan dan kebisingan di Jalan Raya Pantura pada ruas Kecamatan Pucuk -Kecamatan Sukodadi pada tahun 2023.…”
Section: Pendahuluanunclassified